VARIASI SPASIAL DAN TEMPORAL HUJAN KONVEKTIF DI PULAU JAWA BERDASARKAN CITRA SATELIT(SPATIAL AND TEMPORAL VARIATION OF CONVECTIVE RAIN IN JAVA ISLAND BASED ON CITRA IMAGES) - Yetti Kusumawati; Sobri Effendy; Edvin Aldrian (Agromet, 2008)
Convective rain is one of precipitation types that usually occur in Indonesia, result by convective process. This convective rain brings heavy rainfall in short period and could reach a higher intensity than common monsoon rain. Convective process may have a variation with time and location. This research have determined spatial and temporal variation of convective rain in Java island by using the black body temperature (TBB) gradient method based on the GMS-6 (MTSAT-1R) images. As a result, the seasonal convective rain generally occurred in similar period i.e. in the morning from 07.00 to 11.00 LT (local time) and in the evening from 18.00 LT until 05.00 LT. The maximum event occurred from 18.00 LT until mid night. There were different locations between the seasonal convective event. In the seasonal convective rain, there were two spatial patterns. In wet season (DJF) and transitional season from wet to dry (MAM) convective rain spread from east to west Java. While in dry season (JJA) and transitional season from dry to wet (SON), convective rain mostly occurred only in west Java.